THE VIABILITY OF LIFESTYLE AUDITS AS AN EMERGING ANTI- CORRUPTION TOOL IN THE PUBLIC SECTOR: CONCEPTS, ESSENTIALS AND PROSPECTS - Sihanya, Ben (Journal of Anti-Corruption Law, 2023)
Lifestyle audits are viable tools in the fight against corruption. Unfortunately, they have not been sufficiently developed or adopted despite their effectiveness in combatting corruption. For long, countries have deployed diverse anti-corruption strategies under various international, regional and national legal frameworks. Despite these efforts, corruption continues to permeate every sector of national economies, with debilitating effects on development goals and the well-being of populations. Most of the anti-corruption strategies adopted, focus on the integrity of the operational systems of public institutions on the one hand, and personal integrity of their public officials on the other.